Flow Characteristics and Sound Power Transmission Characteristics of Bellows in Pulse Tube Cryocooler - 木松松; 崔晓钰; 殷旺; 黄政; 蒋珍华; 丁磊; 刘少帅; 吴亦农 (Zhileng xuebao)
Compressor outlet tube is a transmission component of sound power, and its sound power loss directly affects the performance of pulse tube cryocooler. Flexible bellows can adjust the relative position of compressors and cold fingers in applications compared to traditional rigid smooth tubes. In order to study the influence of the flexible bellows on the cryocooler, the flow characteristics of two kinds of connected pipes were analyzed by simulation, and the influence of different types of connected pipes on the performance of the whole machine was verified by experiments. The simulation results show that, compared with the rigid smooth pipe, the mixed flow appear at the ripple of the bellows, resulting in more resistance loss. Under the same inlet parameter, the outlet mass flow and pressure amplitude are lower, and the sound power loss is more. The experimental results show that the input power of bellows and smooth tubes is 119 W and 112 W and 279 W and 259 W, respectively, when the cooling capacity is 0.5 W@37.5 K and 3 W@37.5 K. This study provides a reference for the future application of flexible bellows in cryocooler.